Notes on the State-Police Relationship - Baltazar, Edgar (Cuadernos Inter.c.a.mbio sobre Centroamérica y el Caribe, 2020)
With the purpose of doing a theoretical review on the validity of the State as a preponderant political institution and in particular on its policing functions, this essay exposes the state´s elements from the proposal of the Strategic-Relational Approach postulated by Bob Jessop, inspired by contributions of Gramsci and Poulantzas. This approach identifies four substantive elements of the State: population, apparatus, territory and "idea of ​​State". The text describes the relationship between these elements and their relationship with the policing elements; understood in a broad sense, as population and territorial control through the government apparatus and its hegemonic bases, not only as a function of uniformed public force or “low policing”. From this perspective, it is concluded that State is a social relation that provisionally institutes an order of domination supported by the policing functions of controlling bodies, ideas and territories.